Entrepreneurship Training as A Form of Business Development for The People of Sanrobone Village, Takalar Regency - Andi Faisal Bahari (Advances in Community Services Research, 2023)
Technological advances have an impact on all aspects of human life. The economy has not got rid of the impact of technology. Technology provides a variety of facilities for the economy, which undoubtedly greatly supports the existing economic system. One of them is the role of technology in business, which is now known as e-commerce in developing the business further. In today's digital age, student awareness, especially in remote villages, has not been effective in maximizing the use of technology, and most students have smartphones. Although using Internet access is quite possible for a person to interact or even trade in the world of online technology (Internet), it can become a new land for entrepreneurs young to promote and market their products. It is hoped that the socialization of this service team can be the first step for students, especially those in the village, and create new entrepreneurs. The purpose of implementing this socialization is to allow students to have an account in the field of online trading and operate separately.